Implementasi Otomatisasi Tagihan Pembayaran Kos dengan Whatsapp Gateway - Habibah, Az Zahraina Nur; Fiati, Rina; Wijayanti, Esti (Universitas Boyolali, 2024)
This research aims to develop the “Smart Watch Tagihan Kos” application to facilitate the management and monitoring of boarding house bills. The application is designed to efficiently manage room data, resident data, and billing data, with a user-friendly interface. The software development method used is the waterfall method, involving stages of requirement analysis, system design, implementation, system testing, and maintenance. Testing is conducted using the black box approach to test various pages in the application. The results show that Cost Bill Smart Watch System providing an effective solution for boarding house management needs.